The Urge to Hustle: Narratives of Mediated Higher Degree Learning Interaction among University Students during Covid-19 Pandemic - Widya Pujarama (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
The COVID19 has fabricated a new way of life with the worldwide social restrictions policy. During the pandemic, Indonesian university students are mostly socially linked through the Internet, altering their prior face-to-face interactions. While being online, students rely on the technology to create their idealized self as a professional. Alterations in the study methods had created drawbacks when students were continuously building their professional identity, thus their hustle. This research aimed to describe students’ experiences and efforts while treating the Internet as an invisible technology during COVID19. Data collected via online survey with open ended questionnaires by convenience sampling. Research subjects were 10 international class students of Communication Science at Universitas Brawijaya. Data was being analyzed employing thematic analysis. This study found that students’ pressurized effort to hustle and rely more on the self while working to achieve the best mark during the pandemic occurs for two distinct reasons: gradually decreasing trust towards their group members’ teamwork motivation and spiraling compulsion to earn other skills as part of their portfolio before graduating. This research confirms that while students are in the process of adapting to the online learning scheme, their trust level towards online information are heightened yet their trust level towards their peers are weakened. Further studies on the implications of rising hustle culture amongst students to the academic life is suggested. Pembatasan sosial secara global akibat COVID 19 menimpulkan perubahan cara interaksi dalam banyak sisi kehidupan. Selama pandemi, mahasiswa Indonesia terhubung dengan informasi maupun orang lain mayoritas melalui koneksi internet. Perubahan proses komunikasi ini membuat mahasiswa merasa terisolasi dan tertinggal sehingga merasa perlu bekerja lebih keras menyibukkan diri. Penelitian ini bertujuan mendeskripsikan pengalaman dan upaya mahasiswa dalam beradaptasi menjadikan internet sebagai ‘invisible technology’. Pengumpulan data dilakukan melalui convenience sampling dengan menyebarkan kuesioner terbuka dalam survei online. Obyek penelitian adalah 10 mahasiswa Ilmu Komunikasi kelas Internasional di Universitas Brawijaya. Analisis data dilakukan melalui teknik analisis tematik. Temuan penelitian menunjukkan bahwa mahasiswa perlu bekerja lebih keras dalam belajar online karena: berkurangnya kepercayaan terhadap motivasi kerja tim dan juga dorongan bertumbuh untuk mengejar pengalaman yang dapat dimasukkan dalam portofolio sebelum lulus kuliah karena perasaan terisolasi. Penelitian lanjutan mengenai implikasi dorongan psikologis untuk menyibukkan diri di kalangan mahasiswa saat pandemi terhadap kualitas kehidupan akademik lebih mendalam disarankan.